Comparative analysis of biorefinery designs based on acetone-butanol-ethanol fermentation under exergetic, techno-economic, and sensitivity analyses towards a sustainability perspective. (20th May 2021) - Meramo-Hurtado, Samir I.; González-Delgado, Ángel; Rehmann, Lars; Quinones-Bolanos, Edgar; Mehvar, Mehrab
Abstract: Chemical process sustainability has been gaining attention as a comprehensive framework for diagnosing, optimizing, and improving a chemical design. This work presents a comprehensive assessment involving techno-economic, sensitivity, and exergetic factors of two biorefinery configurations for butanol production. The methodology presented here comprises three main steps for assessing biorefinery designs under a mixed techno-economic and exergetic assessment. Firstly, feedstock and processing units were selected based on the defined task (butanol production from lignocellulosic biomass). A general Acetone-Butanol-Ethanol (ABE) fermentation biorefinery was established considering (i) Pretreatment, (ii) Enzymatic hydrolysis, (iii) Fermentation, and (iv) Separation stages. The second step was the process modeling stages, in which biorefineries were simulated using Aspen Plus software, generating several quantitative data to perform economic and exergetic analyses. The last stage of the method is associated with the chemical process sustainability assessment based on techno-economic, sensitivity, and exergy analyses. Biobutanol topology 1 presented a production capacity of 32, 737, 45 kg/h butanol, while topology 2 generated 37, 480 kg/h of this product. Both biorefinery designs had a biomass feed flow of 320, 829 kg/h. The results revealed that both topologies were worthy alternatives from an economic viewpoint, considering the Net Present Value (NPV) 908.74 MM USD for topology 1, and 879.03 MM USD for topology 2. The Return on Investment (ROI) was 29.11% for topology 1 and 37.76% for topology 2. Regarding exergetic analysis, biobutanol topology 1 showed an exergy efficiency of 26.03%. In comparison, topology 2 gives an efficiency of 39.89%.